2013
DOI: 10.13172/2052-0077-2-10-806
|View full text |Cite
|
Sign up to set email alerts
|

Tunnel for ligamentum teres: A rare variation of the liver

Abstract: IntroductionLigamentum teres hepatis, an embryological remnant derived from the obliterated left umbilical vein is lodged on the fissure for the ligamentum teres on the inferior surface of the liver. We report here an anomalous case where the ligament passed through a tunnel instead of a fissure. Case reportThe fissure for ligamentum teres was obliterated by bridging of liver tissue across the quadrate and left lobes. This bridging converted the fissure into a tunnel through which ligamentum teres coursed to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Type IV variants were the most common morphologic variants in our population. These variations have been reported with various names applied to them, such as pons hepatis [5][6]14,16,18,[21][22], absent fissure for ligamentum teres [9,12,17] and ligamentum teres tunnel [10][11]15,19]. We propose the use of standardized nomenclature and classifications, possibly those proposed within this paper.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Type IV variants were the most common morphologic variants in our population. These variations have been reported with various names applied to them, such as pons hepatis [5][6]14,16,18,[21][22], absent fissure for ligamentum teres [9,12,17] and ligamentum teres tunnel [10][11]15,19]. We propose the use of standardized nomenclature and classifications, possibly those proposed within this paper.…”
Section: Discussionmentioning
confidence: 85%
“…There have been reports describing variations of the UF [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22], but a robust classification system was not encountered. We proposed a morphologic classification based on the variations encountered.…”
Section: Discussionmentioning
confidence: 99%
“…Hence the left lobe was continuous with the quadrate lobe. Satheesha et al recently reported a peculiar liver with the total absence of fissure for ligamentum teres and the quadrate lobe (5). A case of liver with the presence of complete tunnel instead of fissure for ligamentum teres on the diaphragmatic surface of the liver with absent quadrate lobe has been reported by Ebby et al (6).…”
Section: Discussionmentioning
confidence: 95%